Animal feed resources for small-scale livestock producers. Proceedings of the second PANESA workshop - Kategile, J.A.; Said, A.N.; Dzowela, B.H. (International Development Research Centre, 1987)
Presents papers on inventory of animal feed resources in Kenya, Tanzania, Ethiopia, Zimbabwe, Malawi, Burundi, Madagascar, Botswana, Swaziland and Mozambique, research and development experiences in Kenya, Tanzania, Burundi and Zimbabwe; socioeconomic aspects of feed resources; and regional/sub-regional research programmes.